The approach and treatment of a unicystic Ameloblastoma in the jaw - doi:10.5020/18061230.2006.p247 - Antônio Francisco Durighetto Júnior; Adriano Mota Loyola; Cláudia Jordão Silva; Sérgio Vitorino Cardoso; Rafaela Guidi; João César Guimarães Henriques; José Humberto Macedo; Leonardo Tadeu Martins (Universidade de Fortaleza, 2012)
Among the complex group of odontogenic tumors, the ameloblastoma points out as the most important and common odontogenic tumor of epithelial origin. It consists mainly of a benign tumor, slow in progress and locally invasive, although it can present high rates of reincidence. The unicystic ameloblastoma is one of the tumor variants and deserves singular consideration for its peculiar characteristics. This study aimed at showing the peculiarities of this ameloblastoma variant through a case report on the care assistance of a young man committed by a jaw tumor, approaching the diagnostic methods used and the applied treatment. Based on present, we conclud that the prognostic for patients with unicystic ameloblastoma is very favorable, since the propaedeutic proceedings are well conducted by the professionals involved.